The First Steps of Migration Legislation and its Consequences in Hungary - Balázs Pálvölgyi (Journal on European History of Law, 2010)
The document delves into the early stages of migration legislation in Hungary and its subsequent impacts, focusing on economic shifts and mass migration trends in the late 19th century. It highlights the liberal period post-1867 Compromise, the influence of liberal rights on political debates around migration, and the modernization efforts under Habsburg governance that fostered economic opportunities and legal reforms, leading to significant socio-economic restructuring and migration patterns within and beyond Hungary.